Solving of Chromatic Number, Chromatic Polynomial and Chromaticity for a Kind of 6-Bridge Graph Using Maplesoft - Tareq Habeeb, Zeyad (Iraqi Journal of Science, 2021)
Maplesoft is a technical computation forms which is a heart of problem solving in mathematics especially in graph theory. Maplesoft has established itself as the computer algebra system for researchers. Maplesoft has more mathematical algorithms which is covering a wide range of applications. A new family ( ) of 6-bridge graph still not completely solved for chromatic number, chromatic polynomial and chromaticity. In this paper we apply maplesoft on a kind of 6-bridge graph ( ) to obtain chromatic number, chromatic polynomial and chromaticity. The computations are shown that graph contents 3 different colours for all vertices, 112410 different ways to colour a graph such that any two adjacent vertices have different colour by using 3 different colour, graph has isomorphic graph which has same chromatic polynomial of graph . The odd number of vertices located in one of these bridges made chromatic number 3. The chromatic number was the important factor that made the number of way 112410. A bijection function created isomorphic graph to graph and the chromatic polynomial of was ( ) ( ).